ChemInform Abstract: Copper(II)‐Catalyzed Cleavage of Carbon—Carbon Triple Bond to Synthesize 1, 2, 3‐Triesterindolizines. Issue 9 (March 2015) - Sun, Jinwei; Hu, Huayou; Wang, Fuyao; Wu, Hui; Liu, Yun
Abstract The title compounds are obtained by reaction of pyridines with butynedioates.